Quality control and quantification in IG/TR next-generation sequencing marker identification: protocols and bioinformatic functionalities by EuroClonality-NGS - Knecht, Henrik; Reigl, Tomas; Kotrová, Michaela; Appelt, Franziska; Stewart, Peter; Bystry, Vojtech; Krejci, Adam; Grioni, Andrea; Pal, Karol; Stranska, Kamila; Plevova, Karla; Rijntjes, Jos; et al. (Leukemia, 2019)
Assessment of clonality, marker identification and measurement of minimal residual disease (MRD) of immunoglobulin (IG) and T cell receptor (TR) gene rearrangements in lymphoid neoplasms using next-generation sequencing (NGS) is currently under intensive development for use in clinical diagnostics. So far, however, there is a lack of suitable quality control (QC) options with regard to standardisation and quality metrics to ensure robust clinical application of such approaches. The EuroClonality-NGS Working Group has therefore established two types of QCs to accompany the NGS-based IG/TR assays. First, a central polytarget QC (cPT-QC) is used to monitor the primer performance of each of the EuroClonality multiplex NGS assays; second, a standardised human cell line-based DNA control is spiked into each patient DNA sample to work as a central in-tube QC and calibrator for MRD quantification (cIT-QC). Having integrated those two reference standards in the ARResT/Interrogate bioinformatic platform, EuroClonality-NGS provides a complete protocol for standardised IG/TR gene rearrangement analysis by NGS with high reproducibility, accuracy and precision for valid marker identification and quantification in diagnostics of lymphoid malignancies.
Keywords: receptory antigenů T-buněk; vysoce účinné nukleotidové sekvenování; reziduální nádor; Immunoglobulins; Neoplasm, Residual; genetické markery; řízení kvality; genová přestavba; Receptors, Antigen, T-Cell; Gene Rearrangement; Humans; Quality Control; Reproducibility of Results; reprodukovatelnost výsledků; výpočetní biologie; Computational Biology; imunoglobuliny; lidé; High-Throughput Nucleotide Sequencing; Genetic Markers